Zero Based Budgeting di Era Digital: Mewujudkan Anggaran Efisien dan Akuntabel Menuju Birokrasi 4.0 - Aldimas Aldimas; Rita Kusuma Astuti; Muhammad Arief Adillah (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the application of the Zero Based Budgeting (ZBB) method in budget management in 2025 as a strategic step to improve efficiency, transparency, and accountability in public financial governance. ZBB is a budgeting approach that requires each organizational unit to prepare a budget from zero without referring to previous allocations, so that each expenditure must be logically justified based on actual needs and strategic priorities. In the context of increasing fiscal pressures and demands for bureaucratic reform, the relevance of ZBB is increasingly strengthening. Using a qualitative approach through literature studies and policy analysis, this study evaluates the effectiveness, constraints, and prospects of ZBB implementation in various government sectors that are undergoing digital transformation, such as immigration services and public services. The results of the study show that although ZBB is able to improve budget efficiency and build a more responsible work culture, its success is highly dependent on the readiness of human resources, reliable information systems, and strong political support. Therefore, the implementation of ZBB in 2025 needs to be accompanied by systematic training, supporting regulations, and an integrated performance evaluation system to produce a significant impact on better budgeting practices.